Risk factors for Clostridioides difficile infection among patients diagnosed with inflammatory intestinal and rheumatological diseases in the biologic era - Helena Martínez-Lozano; Paula Saralegui-Gonzalez; Elena Reigadas; Pablo Ramón Fueyo-Peláez; Aurea García-García; José Miranda-Bautista; Luis Alcalá; Juan Carlos Nieto; María Elena Lobato-Matilla; Ignacio Marín-Jiménez; Patricia Muñoz; Luis Menchén (BMC Gastroenterology)
Abstract Background Clostridioides difficile infection (CDI) in inflammatory bowel disease (IBD) has been associated with poor clinical outcomes. The relationship between biologic therapy and CDI is controversial. We aimed to assess whether biologic therapy increases CDI risk among IBD patients, to identify factors associated with increased CDI risk, and to characterize CDI episodes in our population. Methods We included patients diagnosed with IBD (IBD-cohort) and immune-mediated inflammatory rheumatic diseases (Rheuma-cohort). Risk factors for CDI were assessed using a logistic regression model. We also estimated the incidence rate of CDI for each biologic. Results We included 1866 patients: 1041 from the IBD-cohort and 825 from the Rheuma-cohort. The diagnosis of IBD was the major risk factor for developing CDI in the overall population (OR: 18.29, CI 95%: 5.59–59.80, p < 0.001). Within the IBD-cohort, patients with ulcerative colitis had an increased risk for CDI compared to Crohn’s disease (OR:2.00, 95% CI: 1.18–3.42, p = 0.011). Although the subgroup of IBD patients receiving biologics showed a higher incidence of CDI compared to unexposed IBD patients, biologic therapy was not an independent risk factor for CDI in the logistic regression model; nevertheless, patients who received 3 or more biologic agents had a significantly higher risk for CDI (OR: 3.09, CI 95% 1.13–8.47, p = 0.028). Conclusions IBD significantly increases the risk of CDI among patients treated with biologic therapy; although such treatments do not seem to individually increase the risk, the number of biologics received may be a new predictor of CDI.